2016
DOI: 10.1017/s0021859616000216
|View full text |Cite
|
Sign up to set email alerts
|

Effects of xylanase supplementation on feed intake, digestibility and ruminal fermentation in Rambouillet sheep

Abstract: SUMMARYThe present study aimed to investigate the effects of adding xylanase enzyme (XY) to a basal diet containing 300 g maize stover and 700 g concentrate/kg dry matter (DM) on feed intake, ruminal fermentation, total tract and ruminal digestibility, as well as some blood parameters. Four male Rambouillet sheep (39 ± 1·8 kg body weight), with permanent rumen and duodenum cannulae were used in a 4 × 4 Latin square design. Sheep were fed a basal diet without xylanase addition (control, XY0), or with the additi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 34 publications
0
10
1
Order By: Relevance
“…consistent with the results of McAllister et al (2000), who reported that DM and OM consumption in lambs was not affected by the addition of mixed activity EE products to barley grain-based rations. However, growth performance results obtained from this research don't agree with the findings of Vallejo et al (2016), which reported a significant effect of low and moderate rates of xylanase on feed intake in sheep but not on high concentration. A previous study also reported that the increase in feed consumption with low EE application reflects the increase in ruminal fiber digestion and digesta passage rate (Beauchemin et al 2003).…”
Section: Feed Intake and Growth Performancecontrasting
confidence: 99%
See 1 more Smart Citation
“…consistent with the results of McAllister et al (2000), who reported that DM and OM consumption in lambs was not affected by the addition of mixed activity EE products to barley grain-based rations. However, growth performance results obtained from this research don't agree with the findings of Vallejo et al (2016), which reported a significant effect of low and moderate rates of xylanase on feed intake in sheep but not on high concentration. A previous study also reported that the increase in feed consumption with low EE application reflects the increase in ruminal fiber digestion and digesta passage rate (Beauchemin et al 2003).…”
Section: Feed Intake and Growth Performancecontrasting
confidence: 99%
“…Also, Miller et al (2008) reported no effect on total VFA concentration in the ruminal fluid adding fibrolytic enzymes to barley-based lamb diets. However, enzyme treatment of diets fed to lactating goats or sheep (40% berseem clover and 60% concentrate or 30% maize stover and 70% concentrate, respectively) had a positive effect on total VFA production in the study by Kholif et al (2007) and Vallejo et al (2016). Moreover, Yuangklang et al (2017) reported that the hydrolysis of fiber by enzymes had provided more substrate for microbial production of total VFA and thus increased the concentration of total VFA in the rumen.…”
Section: Rumen Fermentationmentioning
confidence: 94%
“…These agricultural straws contain considerable quantities of cellulose and hemicellulose and has the potential to be a valuable feed source for ruminants, but their nutritive feeding values are limited by their low ruminal degradability. Though the straws could be digested by diverse ruminal microorganisms, the fiber digestibility in rumen is still less than 50% ( Vallejo et al, 2016 ). Consequently, the majority of these agricultural straws are as wastes either left in the field for natural decay or burnt adding to environmental pollution.…”
Section: Introductionmentioning
confidence: 99%
“…This result was similar to the report obtained by Rajabi et al [29] using pomegranate peel extract in fattening lambs as feed supplement. Vallejo et al [30] reported that addition of natural feed additive such as xylanase (at 3 µL/g) to the diets of sheep could reduce excretion of N through fecal and urine.…”
Section: Resultsmentioning
confidence: 99%